Comparative Inhibition of Extrinsic and Intrinsic Thrombin Generation by Standard Heparin, a Low Molecular Weight Heparin and the Synthetic ATIII-Binding Pentasaccharide - Lormeau, Jean-Claude; Herault, Jean-Pascal (Thrombosis and Haemostasis, 1993)
The inhibiting effect of standard heparin, CY216 and the ATIII-binding synthetic pentasaccharide on extrinsic and intrinsic thrombin generation were quantified by evaluating the decrease of the total amount of active thrombin appearing in plasma after triggering coagulation.Heparin as well as CY 216 produced the same quantitative inhibition of extrinsic and intrinsic TGs whereas pentasaccharide inhibited more efficiently extrinsic TG.This pattern of inhibition was further confirmed on pure extrinsic or intrinsic coagulation respectively in factor IX- and factor VII-depleted plasmas.Furthermore, selective suppression of the anti-thrombin activity of CY 216 by limited amounts of PF4 affected the intrinsic TG inhibition more markedly than the extrinsic one.It was concluded that anticoagulant activity produced mainly through thrombin scavenging leads to similar quantitative impairment of extrinsic and intrinsic coagulation, while selective ATIII-mediated factor Xa inhibition results in a more marked effect against the extrinsic system.